Large-Scale Atmospheric Step-and-Repeat UV Nanoimprinting - Kentaro Ishibashi; Hiroshi Goto; Jun Mizuno; Shuichi Shoji (Journal of Nanotechnology)
Step-and-repeat UV nanoimprinting for large-scale nanostructure fabrication under atmospheric pressure was realized using high-viscosity photocurable resin and a simple nanoimprinting system. In step-and-repeat UV nanoimprinting under atmospheric pressure using low-viscosity resin, large-scale nanostructure fabrication is very difficult, due to bubble defects and nonuniformity of the residual layer. To minimize bubble defects and nonuniformity of the residual layer, we focused on the damping effects of photocurable resin viscosity. Fabrication of 165 dies was successfully demonstrated in a 130×130 mm2 area on an 8 in silicon substrate by step-and-repeat UV nanoimprinting under atmospheric pressure using high-viscosity photocurable resin. Nanostructures with widths and spacing patterns from 80 nm to 3 μm and 200 nm depth were formed using a quartz mold. Bubble defects were not observed, and residual layer uniformity was within 30 nm ±10%. This study reports on simple step-and-repeat UV nanoimprinting under atmospheric pressure using high-viscosity photocurable resin, as a very widely available method for large-scale mass production of nanostructures.